2012
DOI: 10.1002/eji.201242610
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional invasion of macrophages is mediated by cysteine cathepsins in protrusive podosomes

Abstract: IntroductionThe ability of macrophages (Mfs) to progress to specific tissues, increase matrix remodeling, and induce angiogenesis is essential for their normal physiological function [1,2]. In addition, tissue infiltration of Mfs is also involved in pathological processes such as chronic inflammation, atherosclerosis, neurodegenerative disorders, and cancer progression [3]. The presence of Mfs Correspondence: Dr. Bojana Mirković e-mail: bojana.mirkovic@ffa.uni-lj.si within tumors is generally a marker of poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 67 publications
(114 reference statements)
2
38
1
Order By: Relevance
“…To begin, we provided evidence that these cells display an enhanced capacity to migrate through dense matrices in an MMP-dependent manner contrasting with our previous observations that 3D migration in dense matrices rather involves cathepsins [45,47,58,59]. While we cannot exclude that chemokines present in cmMTB could be involved in the migration capacity of CD16 + C-D163 + MerTK + pSTAT3 + monocyte-macrophages, we showed that STAT3-dependent acquisition of the M2-like phenotype is essential for the enhanced motility and extracellular matrix remodeling activity in these cells.…”
Section: Discussioncontrasting
confidence: 74%
“…To begin, we provided evidence that these cells display an enhanced capacity to migrate through dense matrices in an MMP-dependent manner contrasting with our previous observations that 3D migration in dense matrices rather involves cathepsins [45,47,58,59]. While we cannot exclude that chemokines present in cmMTB could be involved in the migration capacity of CD16 + C-D163 + MerTK + pSTAT3 + monocyte-macrophages, we showed that STAT3-dependent acquisition of the M2-like phenotype is essential for the enhanced motility and extracellular matrix remodeling activity in these cells.…”
Section: Discussioncontrasting
confidence: 74%
“…2). 17,[57][58][59] In good agreement with podosomes as local sites of matrix degradation, Figure 2. Macrophage podosomes in 2D and 3D.…”
Section: Podosomes In 3dsupporting
confidence: 61%
“…Still, force generation by migrating primary human macrophages on 3D fibrillar collagen has been observed (C. Wiesner et al, unpublished data). 62 To date, degradation of extracellular matrix is the best studied function of 3D podosomes, 17,57,59,62 as described in the following sections. Collectively, these results indicate that 3D podosomes observed in collagen and Matrigel TM networks indeed constitute the 3D counterparts of the classical podosomes found in 2D.…”
Section: Podosomes In 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, macrophage mesenchymal migration is inhibited by protease inhibitors but not by ROCK inhibitors (Van Goethem et al, 2010). In contrast to tumour cell mesenchymal migration, which mainly depends on matrix metalloprotease (MMP) activity, macrophage mesenchymal migration can be mediated by other protease families, including lysosomal cysteine cathepsins (Jevnikar et al, 2012;Van Goethem et al, 2010), in addition to MMPs such as MT1-MMP Wiesner et al, 2013). Macrophage mesenchymal migration, but not amoeboid migration, is also dependent on Hck (Cougoule et al, 2010), Filamin-A (Guiet et al, 2012) and 3D-podosomes .…”
Section: Introductionmentioning
confidence: 99%